Mathematical model of tomographic data dynamic spatial modifications - Книгавко, Ю.В. (Radiotekhnika, 2012)
The developed mathematical model of the patient's face tomographic data changing is described. A new method for computer planning surgical intervention on the human face associated with the movement of volume data, based on the use of continuous and smooth functions is proposed.